BIODIVERSITY OF MICROALGAE AND CYANOBACTERIA IN COTTON FIELD ECOSYSTEMS OF THE TURKESTAN REGION (Experimental biology, 2025)
This study examines the biodiversity of microalgae and cyanobacteria inhabiting the cotton field ecosystems of the Turkestan Region, Kazakhstan. Analysis of soil samples revealed 45 species of microalgae and cyanobacteria, with the highest diversity observed among cyanobacteria, including species from the genera Nostoc and Anabaena. In addition, four pure cultures of microalgae and cyanobacteria were isolated using the enrichment culture method, enabling a detailed investigation of their morphological characteristics and pesticide tolerance. The ecological significance of these organisms lies in their roles in biogeochemical cycles, particularly nitrogen fixation, which is of great importance for the region’s agriculture. To assess photosynthetic activity, an experiment was conducted using the pesticide atrazine, revealing differences in the tolerance of microalgae and cyanobacteria to chemical exposure. The isolated cultures demonstrate potential for use in the bioremediation of contaminated ecosystems and may serve as indicators of pesticide pollution.
Keywords: microalgae; cyanobacteria; biodiversity; pesticides; atrazine